Quantitative determination and validation of avermectin B1a in commercial products using quantitative nuclear magnetic resonance spectroscopy - Hou, Zhuoni (Magnetic resonance in chemistry : MRC, 2014)
Copyright © 2014 John Wiley & Sons, Ltd.